2002
DOI: 10.1080/00420980220119480
|View full text |Cite
|
Sign up to set email alerts
|

Are there Ethnic Enclaves/Ghettos in English Cities?

Abstract: The residential segregation of ethnic groups in urban areas remains an issue of importance for policy-making in multicultural societies, such as England's, with levels of segregation frequently linked to questions of social exclusion and equal treatment. But how segregated are ethnic groups in England? Most studies answer this question using single indices which address one aspect only of a multidimensional concept. In this paper, an alternative approach is used which identifies residential area types accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 20 publications
(13 reference statements)
4
107
0
3
Order By: Relevance
“…Este análisis permitió identificar todos aquellos municipios en los que existen enclaves residenciales según el lugar de nacimiento de la población. A partir de ellos se estableció una categorización teniendo en cuenta tres criterios: Xiana Bueno y Andreu Domingo tipo de enclave residencial: se han seleccionado aquellos municipios que contuvieran secciones censales clasificadas como «enclaves» siguiendo el método propuesto por (Poulsen, et al, 2001;Johnston, et al, 2002) y adaptado para el caso español por Sabater, et al, (2013). Los tipos de enclave fueron calculados según criterios de concentración basados en los diferentes grupos, dando como resultado 6 grupos de los cuales sólo tres estaban representados en Cataluña 1 : (I) Comunidades mayoritarias homogéneas (cuando los nacidos en España representan entre el 80 y el 100% de los residentes en la sección censal); (II) Comunidades mayoritarias no homogéneas (los nacidos en España representan del 50 al 79%); y (III) Enclaves plurales (los nacidos en España representan entre el 30 y el 49%) 2 .…”
Section: Fuentes Y Metodologíaunclassified
“…Este análisis permitió identificar todos aquellos municipios en los que existen enclaves residenciales según el lugar de nacimiento de la población. A partir de ellos se estableció una categorización teniendo en cuenta tres criterios: Xiana Bueno y Andreu Domingo tipo de enclave residencial: se han seleccionado aquellos municipios que contuvieran secciones censales clasificadas como «enclaves» siguiendo el método propuesto por (Poulsen, et al, 2001;Johnston, et al, 2002) y adaptado para el caso español por Sabater, et al, (2013). Los tipos de enclave fueron calculados según criterios de concentración basados en los diferentes grupos, dando como resultado 6 grupos de los cuales sólo tres estaban representados en Cataluña 1 : (I) Comunidades mayoritarias homogéneas (cuando los nacidos en España representan entre el 80 y el 100% de los residentes en la sección censal); (II) Comunidades mayoritarias no homogéneas (los nacidos en España representan del 50 al 79%); y (III) Enclaves plurales (los nacidos en España representan entre el 30 y el 49%) 2 .…”
Section: Fuentes Y Metodologíaunclassified
“…There is a growing literature on the role of processes of migration in forming networks of 'co-ethnics' in host communities (Boyle, Halfacree, & Robinson, 1998;Johnston, Forrest, & Poulsen, 2002). Eve (2010Eve ( , p. 1231) questions ethnicity as the most appropriate focus for analysing 'social integration'.…”
Section: Migration and Networkmentioning
confidence: 99%
“…Using 1991 Census data for the United Kingdom, Champion (1996) reported that in England ethnic minorities are spatially dispersed and that areas with the highest concentrations of ethnic minorities do not match the image of racialised 'ghettos' as known in the USA (see also Peach, 1996;Johnston et al, 2002). In a more recent analysis using the 2001 Census, the national trend of dispersion of ethnic minorities, albeit with pockets of ethnic concentrations, was confirmed by Johnston (2006, p.988).…”
Section: Segregation and Neighbourhood Choicementioning
confidence: 99%